Light Moves Mountains in the Cell. Issue 5 (21st May 2015) - Mehta, Sohum; Zhang, Jin
Abstract : In this issue of Chemistry & Biology, Duan et al. (2015) report the use of a light-inducible protein-protein interaction system to dynamically control the movement of intracellular organelles with spatial and temporal precision in living cells.